Web-Based System for Managing Garage Service And Spare Parts Inventory - Muhammad Danil Hidayat; Pratiwi, Dian; Agus Salim (Penerbitan Universitas Trisakti, 2026)
LangSpeed Motor Garage faces operational challenges, including data inaccuracies and slow manual processes in service and spare parts inventory management, which affect efficiency. This research aims to design, build, and test an integrated web-based management information system to address these problems. The development method used is the Waterfall model, which includes the stages of requirements analysis, system design using UML, code implementation, and system testing. This system was built as a single-page application (SPA) with a modern technology stack, namely ReactJS on the front-end, the serverless Convex backend platform for a real-time database, and Tailwind CSS for interface design. The result of this research is a functional web application that features service management, inventory, and user authentication modules. Based on testing using the Black Box Testing method, all functionality test scenarios were successful with a